Evaluation of registration accuracy between Sentinel-2 and Landsat 8 - Barazzetti, Luigi; Cuca, Branka; Previtali, Mattia (My University, 2016)
Starting from June 2015, Sentinel-2A is delivering high resolution optical images (ground resolution up to 10 meters) to provide a global coverage of the Earth's land surface every 10 days. The planned launch of Sentinel-2B along with the integration of Landsat images will provide time series with an unprecedented revisit time indispensable for numerous monitoring applications, in which high resolution multi-temporal information is required. They include agriculture, water bodies, natural hazards to name a few. However, the combined use of multi-temporal images requires an accurate geometric registration, i.e. pixel-to-pixel correspondence for terrain-corrected products. This paper presents an analysis of spatial co-registration accuracy for several datasets of Sentinel-2 and Landsat 8 images distributed all around the world. Images were compared with digital correlation techniques for image matching, obtaining an evaluation of registration accuracy with an affine transformation as geometrical model. Results demonstrate that sub-pixel accuracy was achieved between 10 m resolution Sentinel-2 bands (band 3) and 15 m resolution panchromatic Landsat images (band 8).
Keywords: Accuracy; Landsat 8; Sentinel-2; Registration